2016
DOI: 10.3892/or.2016.4859
|View full text |Cite
|
Sign up to set email alerts
|

Potential diagnostic value of lncRNA SPRY4-IT1 in hepatocellular carcinoma

Abstract: The manifestation of hepatocellular carcinoma (HCC) involves a multi-factor, multi-step and complex process. Due to the lack of early prediction indices, numerous patients are diagnosed in their late stage. Recently, research in the field of non-coding RNAs (ncRNAs) has changed the original idea that ncRNA genes are just ̔noise̓. Cumulative evidence shows that long non-coding RNAs (lncRNAs) among ncRNAs play an increasingly important role in epigenetics, pre-transcription and post-transcription. In the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 42 publications
4
38
0
Order By: Relevance
“…Studies have suggested that SPRY4-IT1 may act as molecular scaffolds for protein complexes that lack protein-protein interaction domains or can interact directly with microRNAs and prevent them from binding to mRNA, thus regulating protein synthesis [10]. In the aspect of cancer studies, SPRY4-IT1 dysregulation was found to be closely associated with tumor development and also contributed to cell proliferation, cell apoptosis and cell invasion and cell migration in different types of cancers [10, 1214, 17]. These findings may suggest the critical function of SPRY4-IT1 in cancer progression and SPRY4-IT1 may serve as a novel biomarker for early diagnosis and prognosis in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that SPRY4-IT1 may act as molecular scaffolds for protein complexes that lack protein-protein interaction domains or can interact directly with microRNAs and prevent them from binding to mRNA, thus regulating protein synthesis [10]. In the aspect of cancer studies, SPRY4-IT1 dysregulation was found to be closely associated with tumor development and also contributed to cell proliferation, cell apoptosis and cell invasion and cell migration in different types of cancers [10, 1214, 17]. These findings may suggest the critical function of SPRY4-IT1 in cancer progression and SPRY4-IT1 may serve as a novel biomarker for early diagnosis and prognosis in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SPRY4-IT1 expression was upregulated in the plasma from HCC patients suggesting this one to be a good diagnostic biomarker. Combination of SPRY4-IT1 and AFP (the cut-off value of AFP was at 200 ng/mL) possessed a moderate ability for discrimination between HCC patients and controls; the area was equal to 0.80 [108] . Highly upregulated in liver cancer (HULC) lncRNA has been implicated in the regulation of hepatoma cell proliferation, since it induces HCC cells to activate EMT and then promotes tumor progression and metastasis through the miR-200a/ZEB1 signalling pathway [109] .…”
Section: Circulating Non-coding Rnamentioning
confidence: 99%
“…Jing et al 18 performed the quantitative reverse transcription polymerase chain reaction (qRT-PCR) assay in 87 pairs of HCC tissues and found that SPRY4-IT1 was remarkably elevated in tumor tissues compared with nontumor tissues. The high level of SPRY4-IT1 was positively associated with tumor differentiation, tumor size, and TNM stage.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%